Pengaruh Dana Pihak Ketiga, Capital Adequacy Ratio, NonPerforming Loan, Suku Bunga, Bopo Dan Roa Terhadap Penyaluran Kredit Bank Umum Yang Terdaftar Di Bursa Efek Indonesia - Elidawati; Wijaya, Handoyo; Harahab, Sunarji; Sumarson Goh, Thomas (STIEM BONGAYA, 2023)
The purpose of this study was to determine and analyze the effect of third party funds, capital adequacy ratio, non-performing loans, interest rates, BOPO and ROA on credit distribution of commercial banks listed on the Indonesia Stock Exchange. The population is 43 commercial banks listed on the Indonesia Stock Exchange for the 2017-2020 period. The research sample is 21 Commercial Banks listed on the Indonesia Stock Exchange for the 2017-2020 period. In this study, the techniques used in data collection are documentation study methods and literature study methods. This study uses multiple linear regression analysis. The results of the study indicate that third party funds, capital adequacy ratio, non-performing loans, interest rates, BOPO and ROA have an effect on lending to commercial banks listed on the Indonesia Stock Exchange